Chiral nanoscale pores created during the surface explosion of tartaric acid on Cu(111). Issue 99 (23rd November 2016) - Therrien, A. J.; Lawton, T. J.; Mernoff, B.; Lucci, F. R.; Pushkarev, V. V.; Gellman, A. J.; Sykes, E. C. H.
Abstract : The autocatalytic decomposition of tartaric acid on Cu(111) exhibits unique kinetics, which are linked to a hexagonal surface structure adopted at high coverage. Abstract : The autocatalytic decomposition of tartaric acid on Cu(111) exhibits unique kinetics, which are linked to a hexagonal surface structure adopted at high coverage. The chirality imposed on the surface by tartaric acid throughout the explosion process is presented, and the hexagonal structure shows promise as a chiral template for enantiospecific surface chemistry.